Nahdlatul Wathan and The 2019 Presidential Election - Parhanudin, Muh. Alwi; Azmi, Elisatun (UIN Mataram, 2023)
This study aims to determine the existence of the Nahdlatul Wathan Islamic community organization and its impact on the election of President and Vice President in the 2019 simultaneous general election in Pringgasela Village. The analysis in this study uses Social Movement Theory and Rational Choice Theory. This study used a qualitative approach, with data collection techniques obtained from observations, interviews of data sources, and documentation. By using an attractive model consists of three stages: data reduction, data presentation and conclusions. The results of this study show that the existence of the Nahdlatul Wathan organization in Pringgasela Village cannot easily affect the victory of the presidential and vice-presidential candidates’ number 01 in 2019 in Pringgasela Village. The factors that led to the defeat of the Presidential and Vice-presidential candidates’ number 01 (Jokowi-Ma'ruf Amin) such as the mobilization of the Nahdlatul Wathan management were not optimal, the influence of the media at that time, antipathy towards Jokowi, people who voted with calculation and suitability.